Impactos territoriais dos assentamentos rurais no Município de Esplanada – BA - Costa Neto, Antonio de Oliveira (2016)
The present work aims to analyze the territorial impacts caused by the implementation of agricultural settlement in the Municipality of Esplanada — BA. To accomplish this objective it was necessary analyze relevant themes inside the Brazilian agricultural issue, like struggle for land, land structure and the government‘s role in the settlement consolidation process, above all the role of the Instituto Nacional de Colonização e Reforma Agrária (INCRA, Colonization and Agricultural Reform National Institute), main responsible for the implementation and support to the development of Brazilian agricultural settlements. The struggle for land in Esplanada was strongly marked by the presence of a fray, who, when assumed the role of leader of the peasants, managed to influence the implementation of five settlements. The land structure of Esplanada present relative values close to Brazil and Bahia. Those values show high concentration of lands and poor distribution of agricultural areas, where the latifundium, besides having the biggest area percentage, continue to expand. Despite the settlement implementation, the high concentration of areas continue. The government with a timid settlement creation policy by dispossession cannot decentralize lands. Many of those settlements, like the ones form the Municipality in this study, find themselves only in the created settlement category, far away from becoming consolidated. The INCRA cannot execute its role effectively, having strong influence in the development of these settlements. Despite the problems face by the settlers, the territorial impacts caused by the settlement implementation are many. Those considerably improved their lives regarding to education, dwelling, alimentation and income. Moreover, the settlements also provided a new socioeconomic dynamic in the Municipality. In this context, are evident the positive impact of the settlements in the lives of the settlers, whom are completely inserted in the Municipality development.